Comparing Student Learning From and Perceptions of Open and Commercial Textbook Excerpts: A Randomized Experiment - Clinton, Virginia; Legerski, Elizabeth; Rhodes, Bri (Frontiers in Education, 2019)
Open textbooks, which provide students with electronic access to texts without fees, have been developed as alternatives to commercial textbooks. Building on prior quasi-experiments, the purpose of this study is to experimentally compare an open and commercial textbook. College students (N = 144) were randomly assigned to read an excerpt from an open or commercial textbook, answer questions about content, and indicate their perceptions of textbook quality. Learning was similar between textbook types. Perceptions differed in that the discussion of research findings was reported as higher quality in the open textbook while the visuals and writing were reported as higher quality in the commercial textbook. Neither perceptions of research findings nor visuals correlated with learning performance. However, perceptions of writing quality and everyday examples were correlated with learning performance. Findings may inform initiatives for open textbook adoption as well as textbook development, but are limited due to the use of an excerpt. Reading to learn is a fundamental activity for knowledge construction (Duke et al., 2003; Alfassi, 2004; Maggioni et al., 2015). Textbooks are common educational tools for reading to learn, even in the digital age (Fletcher et al., 2012; Knight, 2015; Illowsky et al., 2016). The rising cost of commercial textbooks, along with the affordances of the internet and growing interest in expanding access to knowledge, has brought about the development of open textbooks, which students can access electronically without cost (Smith, 2009). There have been multiple studies indicating that students' learning from and opinions of open textbooks are similar to or better than those of commercial textbooks (e.g., Clinton, 2018; Lawrence and Lester, 2018; Medley-Rath, 2018; Cuttler, 2019; Grissett and Huffman, 2019). However, these studies have all been quasi-experimental or correlational; therefore, causal claims were not possible. Moreover, students in these studies were aware that the open textbooks were free whereas the commercial textbooks were not, which could bias their attitudes (Clinton, 2019). An experimental examination with participants who are naive to the cost of the textbook would address the confounds related to student awareness of cost. The purpose of this experiment is to examine students' learning from and perceptions of an open textbook compared to a commercial textbook.